Pattern of recovery and outcome after stroke in patients accessing a Western Cape rehabilitation facility - Rouillard, Susan (Department of Health and Rehabilitation Sciences, 2025)
Background: Stroke is a growing healthcare problem in South Africa, and contributes significantly to theburden of disease. Rehabilitation is thought to improve recovery and outcome, but little is known about current rehabilitation practices and outcomes in the South African setting. Aims and Objectives: The primary aim was to describe pattern of recovery and outcome after stroke in first ever stroke patients at a Western Cape Rehabilitation Facility. The secondary aim was to explore factors that may influence outcome after stroke. Objectives included describing characteristics of stroke patients the rehabii itation process, and certain aspects of the environment. Study Design: The study was a prospective, longitudinal, descriptive study of first ever stroke patients admitted to the Western Cape Rehabilitation Centre between 22 June 2005 and 28 March 2006. Instrumentation: The ational Institute of Health Stroke Scale IHSS) was used to describe severity on admission. The Barthel Index (BI) and Rivermead Motor Assessment (RMA) were used to describe functional and motor recovery respectively. The main outcome measure at six months was the Modified Rankin Scale (MRS), with secondary outcomes including the ottingham Extended Activities of Daily Living Scale, the Caregiver Strain Jndex and the EQ-5D, a measure of health related quality of life. Questionnaires drawn up for use in the study collected further information on patient characteristics, residential and work status at six months, as well as environmental features. Procedure: Patients who met the eligibility criteria were assessed at admission discharge and six months post stroke. Data Analysis: Summary statistics were used to present descriptive data. Friedmans analysis of variance and Wilcoxons matched pairs test were used to assess the significance of change across the selected measurement points. A repeated measures A OYA was used to investigate differences in pattern of recovery between sub-groups. Bivariate analysis and logistic regression were used to analyse the influence of certain factors on MRS scores at six months. Results: Participants were noted to be younger (average age of 51.3 ± I 4.4 SD) than those in overseas rehabilitation studies with a high proportion of haemorrhagic strokes and infective aetiologies. Participants were mostly from low income homes although the majority lived in formal housing (86.3%) with access to services. The rehabilitation process was characterised by early admission after stroke (74.5% within 30 days), and an average length of rehabilitation stay of approximately 60 days. Four participants were readmitted for further rehabilitation stays within the six month follow up period. Of the remaining patients, fewer than I 0% had received any substantial rehabilitation input after discharge, although most had been seen at least once by a health professional (89.4%). The overall pattern of recovery showed change between all three time points with most change occurring between admission and discharge (median Bl change of 25, p<0.017). However, clinically significant change (defined by> 15% of total scores) was seen between discharge and six months in terms of Bl scores in 55.3% and RMA Gross Sub-scale scores in 45.5% of participants. Mobility items reflected the most change with 81.8% of participants independently mobile at six months compared to 54.5% at discharge. The pattern of recovery over time did not appear to be influenced by severity of stroke (F=2.29, p>0.05) or early/late admission to rehabilitation (F=0.51, p>0.05). Only one participant was living in an institution at six months, despite the fact that more than 20% of participants required constant care. The majority of participants (59.6%) were independent in self-care but many required assistance for extended activities of daily living such as housework, meal preparation, using public transport and shopping. Of interest were difficulties experienced with community mobility, a high prevalence of depression or anxiety (50%) as well as problems with relationships or feelings of isolation (82.6%). High levels of caregiver strain were reported in 55.8% of caregivers. Only 10% of those working prior to their stroke had returned to work at six months. Severity of stroke (fHSS) emerged as the clearest predictor of outcome (OR 0.70, CJ 0.53-0.94), but environmental factors were also seen to be significant. Income group affected outcome (adj z=-2.08, p<0.05), and the presence of at least one reported environmental barrier reduced the odds of favourable recovery according to the MRS (OR 0.18 Cl 0.03-0.98). Lack of transport and financial problems were highlighted by participants as major barriers affecting participation. Discussion and Conclusions: Pattern of recovery followed a more or less expected course over time with greater change between admission and discharge, than between discharge and six months. The high percentage of participants improving between admission and discharge suggests appropriate selection of rehabilitation candidates and effectiveness of the rehabilitation programme. Clinically significant change occurring between discharge and six months particularly with regard to higher mobility, implies that patients may benefit from follow up after discharge in order to optimize outcomes, especially as many participants were discharged fairly early after their strokes while recovery may still be ongoing. In terms of outcomes, BJ scores at six months were comparable to other studies, with most patients functionally independent or requiring only minimal assistance with activities of daily living (ADL). However, a higher prevalence of difficulties was seen in more complex extended ADL and at the level participation restrictions than in studies in developed countries. In particular, there were higher levels of depression, social isolation and caregiver strain, and only a small percentage of those previously working had returned to work at six months. Lack of community mobility and difficulties with transport may have contributed to restrictions in participating in activities outside of the home. These difficulties are most likely to arise after discharge from rehabilitation, as the patient tries to resume pre-stroke roles in the community. Further research is recommended to determine whether provision of follow up after discharge from rehabilitation will improve outcomes. Research is also recommended to explore how caregivers can be best supported to reduce levels of caregiver strain. Although the severity of stroke at admission was found to be the clearest predictor of outcome, the influence of adverse environmental factors on outcome was also apparent. Other characteristics of the study sample such as the young age distribution and medical profile may also have contributed to differences in recovery and outcome.